Pelayanan dan Penanganan Anak Berkebutuhan Khusus di SD Karakter Anna Cendikia Insani - Ananda Sephia Anisati; Nova Estu Harsiwi (Faculty of Educational Sciences,Universitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2023)
Inclusive education is an educational service system that requires children with special needs to study at nearby schools in regular classes with their friends. Children with special needs are children who need special services to be able to carry out their daily lives. When a child has a different condition from other children, he needs special treatment or services to help him.This study aims to find out what services and treatment are given to children with special needs at Anna Cendikia Insani Character Elementary School. The subjects of this study were class I homeroom teachers and students with special needs at Anna Cendikia Insani Character Elementary School.The research methods used in this research are observation, interviews, and documentation. Observations were made by directly visiting Anna Cendikia Insani Character Elementary School. Interviews were conducted with informants, namely the homeroom teacher of class I. Documentation was carried out by taking pictures at Anna Cendikia Insani Character Elementary School.The results obtained are that children with special needs at Anna Cendikia Insani Character Elementary School are served by implementing learning in the same classroom as other friends. The services provided during learning are different from other normal children. Obstacles experienced in teaching children with special needs were found, but they could be handled by existing educators.